Primacy in the Church — an official Position of the Russian Orthodox Church and continuation of the orthodox-catholic dialogue - Матић, Златко (Sabornost - The Theological Year-book, 2014)
Having studied the Ravenna document, the Russian Orthodox Church disagreed with it in the part that refers to synodality and primacy on the level of the Universal Church. Members of the Holy Synod of Russian Orthodox Church (ROC), during the meeting at 25–26 December 2013, are adopted official document Position of the Moscow Patriarchate on the problem of primacy in the Universal Church. The aim of this paper is to present and analyze, for the future of the ecumenical dialogue, very important document of ROC. The supplement brings the document translate in the Serbian language.